FACTOR THAT AFFECTS REPURCHASE INTENTION AMONG SHOPEE CUSTOMERS IN WEST JAKARTA (SATISFACTION AS A MEDIATOR) - Anggelina, Chyntia; Ruslim, Tommy Setiawan (Graduate Program of Universitas Tarumanagara, 2023)
Digital technology is currently very developed, one of which is the business sector, namely e-commerce, many people are facilitated by this e-commerce. Customer doesn’t need to come to the store by himself, he/she just use e-commerce and order directly online, the items we ordered will be sent immediately. This has started to become a new culture, especially in Indonesia, with the existence of e-commerce it can also save time as we know we can make transactions through e-commerce anytime and anywhere without having to meet the seller in person. This study aims to examine whether there is an effect of perceived quality, perceived value, perceived popularity, web design quality on Shopee consumer's repurchase intentions in West Jakarta (with satisfaction as a mediation). There are 234 respondents who are Shopee consumers in West Jakarta. The method used in this research is non-probability sampling by distributing online questionnaires via Google Form, then the data obtained is processed using SmartPLS version 3.2.9. From the processed results it was found that there was an effect of perceived quality, satisfaction, perceived popularity on repurchase intentions, and there is no effect between web design quality and perceived value on repurchase intention.